"Looking garbage in the eyes": From recycling to reducing consumerism- transformative environmental education at a waste treatment facility. Issue 6 (2nd November 2021) - Goldman, Daphne; Alkaher, Iris; Aram, Iggy
Abstract: Making people aware of the interconnections between personal consumerism and its environmental consequences is fundamental for motivating them to engage in more environmentally responsible consumption practices. This interpretive study, conducted in 2018, explored how transformative sustainability learning is implemented in waste education conducted at an environmental education center within the largest waste-treatment facility in Israel, and if it initiates a transformative process. Educators were selected since they serve as societal change-agents. Data were collected from learning plans developed by the center, observations, and interviews of participants (150) during and after their visit. Findings indicate that the educational intervention comprised a "key experience", initiating a transformative process, and elicited a framework of characteristics for transformative waste education. In view of the role of consumer society in contemporary waste-related challenges, the principles emerging from this study may provide a model for other such centers, based on critical waste education that may motivate behavioral change.